INOVASI MINUMAN DAN PANGANAN BERBAHAN BAKU BIDARA LAUT (XIMENIA AMERICANA) DAN MANGROVE DARI PESISIR KOTA BATAM - Ramses Ramses; Erwin Ashari; Ramdani Ramdani (Universitas Lancang Kuning, 2018)
Bidara Laut Plant, Ximenia americana L., is one of coastal vegetation that potentials to be expanded as various healthy drink innovative products and gives a promises to be expanded in the future due to its health benefits and has never been produced. The activity was conducted at Sarang and Mecan Islands, Sekanak Raya sub-district, Belakang Padang district, Batam, in companion with Sarang and Mecan “Kompang” Conservation group. The Activity was started from May up to October 2018. Implementation methods were counseling, training and production practices, demonstration plots, strengthening management and business development through Focus Group Discussion (FGD). This activity has succeeded in improving partner communities’ skills in making processed beverages and meals made of Bidara Laut and mangroves fruits. It was a new knowledge for the community in sustainable usage and environmental conservation, especially mangrove resources. Processed innovations types which produced were Bidara Syrup, Bidara Pudot, Bidara Fresh Drinks, Jeruju Stick, Jeruju Layer Cakes, and Komojo Sponge cake, which all these processed mangrove and Bidara products have own exclusivity and beneficial to health. For their sustainability guarantee, mangrove seedling and Bidar Laut X. americana farming were created together with partner community.